Building an Environmentally Conscious Generation: Implementation of Geography Learning in High Schools - Ikbal Moh Sahban; Uwakwe Igbokwe; Matilda Kanyampa Nakazwe (Journal of Social Knowledge Education (JSKE), 2024)
Purpose of the study: To find out the application of geography learning at State Senior High School 1, South Dampal and to find out the application of environmental care attitudes in schools that are applied to students at State Senior High School 1, South Dampal. Methodology: This study uses a descriptive method with a qualitative approach. The population in this study were students of class XI social sciences with a sample of 93 people. Data collection techniques with questionnaires and observations. The data management technique is by means of qualitative descriptive using the percentage formula Main Findings: Based on the results of data analysis, it was found that geography learning for students of class XI social sciences at State Senior High School 1 Dampal Selatan, has been running well. In addition, the application of geography learning to environmental awareness is quite good, some students care about the environment at school and some students do not care about the environment at school. Novelty/Originality of this study: This study shows that the implementation of structured and interactive geography learning can effectively instill an attitude of environmental concern among high school students, forming a generation that is more aware of the importance of preserving nature. Through this study, it is proven that a geography learning approach that integrates real environmental issues can increase students' awareness and responsibility for environmental preservation.